Effect of natural convection on 3D MHD flow of MoS2-GO/H2O via porous surface due to multiple slip mechanisms - Pandey, Alok Kumar; Upreti, Himanshu; Joshi, Navneet; Uddin, Ziya (Journal of Taibah University for Science, 2022)
The theme of this work is to examine the magnetized flow behaviour of hybrid nanofluid containing molybdenum disulphide (MoS 2 ) and graphene oxide (GO) nanoparticles subject to multiple slip mechanisms, natural convection and chemical reaction of mth order. The working hybrid nanofluid is prepared by an amalgamation of nanoparticles, i.e. MoS 2 and GO and conventional fluid (H 2 O). The existing equations of the model were solved by the techniques, i.e. shooting and bvp4c. To validate our codes, the comparison was presented by previous research. Here, we observed that, with an increase in thermal slip parameter values, only the thermal field profiles of MoS 2 -GO/H 2 O regularly depreciated. Moreover, when there was augmentation in velocity slip parameter, temperature and concentration functions rose, while both velocity outlines of MoS 2 -GO/H 2 O fluid declined. Furthermore, the velocity functions of MoS 2 -GO/H 2 O augmented and the concentration function declined with an increase in natural convection parameter values.